Celebrity Endorser, Product Quality Mempengaruhi Niat Beli Pada E-Commerce Melalui Brand Trust - Putri, Indri Destika; Hadi, Effed Darta (Universitas Islam Kadiri, 2023)
This research aims to test whether Celebrity Endors and Product Quality can partially influence Purchase Intentions in E-Commerce or purchase intentions, as well as the role of brand trust in mediating this influence. This research has a population, namely consumers of Scarlet products, while the sample is 149 consumers of Scarlet Whitening in Bengkulu who were obtained using a questionnaire, and selected through a non-probability sampling technique, namely convenience sampling. Data analysis used using the PLS SEM method for the Smart PLS program. The research results show that Celebrity Endors have a significant and positive influence on brand trust, Product quality has a significant and positive influence on brand trust, Brand trust has a significant and positive influence on purchase intention, Product quality has a significant and positive influence on purchase intention, Celebrity Endors does not have a significant influence on purchase intention through brand trust and Product Quality has a significant influence on purchase intention through brand trust.